Consolidating the social health insurance schemes in China: towards an equitable and efficient health system - Meng, Qingyue; Fang, Hai; Liu, Xiaoyun; Yuan, Beibei; Xu, Jin (The Lancet (British edition), 2015)
Fragmentation in social health insurance schemes is an important factor for inequitable access to health care and financial protection for people covered by different health insurance schemes in China. To fulfil its commitment of universal health coverage by 2020, the Chinese Government needs to prioritise addressing this issue. After analysing the situation of fragmentation, this Review summarises efforts to consolidate health insurance schemes both in China and internationally. Rural migrants, elderly people, and those with non-communicable diseases in China will greatly benefit from consolidation of the existing health insurance schemes with extended funding pools, thereby narrowing the disparities among health insurance schemes in fund level and benefit package. Political commitments, institutional innovations, and a feasible implementation plan are the major elements needed for success in consolidation. Achievement of universal health coverage in China needs systemic strategies including consolidation of the social health insurance schemes.